The use of learner response systems in the classroom enhances teachers' judgment accuracy. (December 2018) - Zhu, Chunjie; Urhahne, Detlef
Abstract: The study aimed to support student achievement and teacher judgment accuracy by the use of learner response systems ("clickers") in the classroom. Twenty school classes with 459 sixth-grade students and their mathematics teachers were divided into three groups for a quasi-experimental pre-post-test intervention study over five weeks. Students of the clicker group gained more mathematical knowledge from the intervention than students of the diary and control group. Teacher judgments of all three groups were getting more accurate. However, teachers using clickers judged with far the highest accuracy. Clickers can be recommended as a valuable tool for enhancing teacher judgment accuracy. Highlights: The study aimed to support student achievement and teacher judgment accuracy. Sixth-grade students used learner response systems ("clickers") in the classroom. A five-week intervention study with two comparison groups was conducted. Students of the clicker group showed the highest test performance. Teachers of the clicker group made by far the most accurate judgments.